Cultural Tourism and Ecotourism Empowerment in the Sustainable Tourism Development and Destination Competitiveness Enhancement - WARDANA, I Made; SUKAATMADJA, I Putu Gde; YASA, Ni Nyoman Kerti; ASTAWA, I Putu (Journal of Environmental Management and Tourism, 2019)
The research aims to investigate the influence of cultural tourism and ecotourism empowerment on sustainable tourism development and tourism competitiveness as a long term perspective tourism development model. The research is conducted on the tourism in Bali Province that based on culture and natural beauty. The research uses quantitative approach with 147 respondents as sample. Data collection uses questionnaire. Respondents consist of the management of tourism travel agents, hospitality industry, restaurant, academics and government. Data are analyzed using Structural Equation Modelling (SEM) through partial least square approach. The research findings demonstrate that cultural tourism and ecotourism have positive and significant influence on sustainable tourism development efforts. Cultural tourism and sustainable tourism development have positive and significant influence on destination competitiveness. Ecotourism is directly having no significant influence on destination competitiveness but it is indirectly having a significant influence on competitiveness through sustainable tourism development. Further, the research also gives direction that local community support is able to moderate the relationship between cultural tourism and ecotourism and sustainable tourism development. The research results give an indication that cultural preservation, natural environment, social environment, and local community participation are the upmost elements in sustainable tourism development model and destination competitiveness enhancement.